Immunolocalization of soluble guanylyl cyclase subunits in rat kidney - Mundel, Peter; Bachmann, Sebastian; Kriz, Wilhelm; Gambaryan, S.; Koesling, D. (Histochemistry and cell biology, 1995)
Stimulation of soluble guanylyl cyclase (SGC) by nitric oxide (NO) results in the generation of cyclic guanosine monophosphate (cGMP). We recently described expression of abundant nitric oxide synthase, the enzyme by which NO is generated froml-arginine, in macula densa cells of rat kidney at the protein and mRNA level. In the present study we looked for possible targets of NO in the kidney. By light and electron microscopy, we applied polyclonal antisera against four subunits (α1,α2, β1β2) of SGC in immunocytochemical studies of frozen sections of rat kidney. We demonstrate the presence of α1-subunit in glomerular podocytes and of β2-subunit in principal cells of the collecting duct. In both cell types a cytosolic localization was evident from ultrastructural analysis. Regarding the collecting duct, NO was shown by other authors to inhibit sodium reabsorption in cultured mouse cortical collecting duct principal cells. In podocytes NO may relax the contractile system of podocyte foot processes, the tone of which has been suggested to counteract the elastic distension of the capillary wall.
Gesehen am 30.11.2023